The mediating role of participation on bonding, bridging and linking social capital and empowerment toward community development: a study among squatter settlements in Tehran, Iran - Ahmad, Nobaya; Babaei, Hamidreza; Gill, Sarjit S. (Penerbit Universiti Malaysia Terengganu, 2013)
The importance of social capital and its dimensions-bonding, bridging and linking social capital - and the role of participation in promoting empowerment in poor people, especially among squatter settlements, is widely recognized as the main aim of community development. The aim of this study is to test an exploratory model of empowerment in a sample of squatter settlements in Tehran, Iran, by examining the mediating role of participation in the relationship between bonding, bridging and linking social capital. The sample comprised of 328 poor people in two communities from Iran, which were randomly selected for the study. A questionnaire was used as the data collection method and the stratified random sampling technique was employed. The exploratory model, including all hypothesized variables, provided an adequate fit (x^2=29.24; df=17; p=.052; adjusted goodness-of-fit index [AGFI] =.96; goodness-of-fit index [GFI]=.98; rootmean- square error of approximation [RMSEA]=.05) for the data and indicated that participation did not fully mediate the relationship between bonding and bridging social capital and empowerment. The influence of bonding and bridging social capital on empowerment was mediated through participation among squatter settlements in Tehran, Iran. However, social capital is seen as a good thing in empowering people and encouraging their participation for community development, as it can build strong correlation with economic prosperity, stable governance and social cohesion. For community workers, especially, bridging capital can be seen as important for managing diversity and maintaining community cohesion, whereas linking capital is seen as a thing for empowerment and partnership working. Furthermore, the lack of linking social capital may receive more attention from policy makers. There are various sources that squatter settlements may communicate through local and governmental organizations, for example participating in local elections for neighborhood organizations such as 'Shora'.